ACADEMIC LIFE SATISFACTION SCALE (ALSS) AND ITS EFFECTIVENESS IN PREDICTING ACADEMIC SUCCESS - P.K. Sudheesh Kumar and Dileep. P
The study is undertaken to examine the effectiveness of a newly constructed psychometric instrument to assess Academic Life Satisfaction . Along with the components of Emotional Intelligence Academic Life Satisfaction Scale is used to predict the scholastic achievement as an index of Academic success. The investigators found that Academic Life Satisfaction is the best predictor of Achievement in social studies of secondary school pupils in Kerala.